Effects of ovarian reserve and hormone therapy on hearing in premenopausal and postmenopausal women: A cross-sectional study. (May 2018) - Zhang, Jingfei; Zhang, Tingyue; Yu, Lisheng; Ruan, Qianying; Yin, Lingxue; Liu, Dong; Zhang, Haicheng; Bai, Wenpei; Ren, Zhenghong
Highlights: To our knowledge, this is the first study in which AMH level was measured to evaluate the effect of ovarian reserve on hearing. To determine the early changes in hearing loss among pre- and postmenopausal women, we performed extended high-frequency audiometry. A decline in ovarian function is associated with hearing loss, especially in relation to extended high-frequency air conduction of the right ear. Preserving ovarian function and reducing earphone use are important measures to protect women's hearing. Abstract: Objectives: To observe the hearing function around menopause, to analyze the effects of ovarian reserve and hormone therapy on hearing, and to study factors related to hearing loss among women around menopause. Study design: In this cross-sectional study, we evaluated 109 women around menopause aged 45–55 years, including 40 women with ovarian failure, 48 with ovarian non-failure, and 21 receiving hormone therapy. All women underwent an audiologic evaluation, and hormone blood testing was performed. The general condition, reproductive history, medical history, lifestyle, and menopausal symptoms were collected through a questionnaire. Main outcome measure: The auditory threshold and anti-Mullerian hormone level. Results: Women in the ovarian failure group presented with a decreased hearing level in all frequency bands compared with those in the ovarian non-failure group; the significant differences occurred at 8000 Hz, 10 000 Hz, 12 500 Hz, and 16 000 Hz in the right-ear air conduction. The auditory threshold was lower in the hormone therapy group than in the ovarian failure group, but the difference was statistically significant only in the right-ear air conduction at 10 000 Hz. There were two risk factors for hearing loss: an anti-Mullerian hormone level <0.01 ng/mL (odds ratio [OR] = 2.624) and frequent earphone use (OR = 3.846). Conclusions: A decline in ovarian function is associated with hearing loss in women, especially in relation to extended high-frequency air conduction of the right ear. Preserving ovarian function and reducing earphone use are important measures to protect women's hearing. However, the effect of hormone therapy on hearing requires further investigation.